The effectiveness of a training program based on self-determination theories in developing decision-making skills among students with learning disabilities - AL-JABALI, AHMAD ALI (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the effectiveness of a training program based on theories of self-determination in the development of decision-making skills of students with learning difficulties, the study used a semi-experimental approach, and the study population consisted of all students with learning disabilities in Ajloun (Kufranja), the sample consisted of (30) 15 students as an experimental group and 15 students as a control group. The researcher also prepared a training program based on self-determination theories to develop decision-making skills. The results showed a weak score for the self-determination scale of the experimental and control groups in the pretest scale, and an average score for the experimental group in the post-test and The study recommended: Developing a program to promote self-determination and decision-making at all educational levels for students with learning disabilities and holding sessions and workshops to guide parents to inform them of the developmental, social and psychological characteristics of students with learning disabilities and how to deal with them.